DICHOTOMY OF BPJS REGULATIONS WITH LAW NO. 17 OF 2023 WHICH CAUSES THE LOSS OF THE FUNCTION OF GENERAL DENTISTS IN BPJS SERVICES IN HOSPITALS - Amri Ul Ikhwan; Redyanto Sidi (PT. Radja Intercontinental Publishing, 2025)
This study examines the existence of a dichotomy or disharmony of regulations between the Social Security Administering Body (BPJS) and several other regulations including Law No. 17 of 2023 concerning Health, especially in the context of the role and function of general dentists in health services based on the National Health Insurance (JKN). After the enactment of Presidential Regulation (Perpres) No. 59 of 2024 concerning the Third Amendment to Presidential Regulation Number 82 of 2018 concerning Health Insurance (Perpres 59/2024), new provisions have emerged that implicitly or explicitly limit the scope of general dentist practice in BPJS services, including in promotive, preventive, curative, and rehabilitative aspects. The disharmony between BPJS technical regulations and the mandate of the latest Health Law has caused unrest in the field, both at the health facility level and dentists, and also the community as patients. This study uses a juridical-normative approach with an analysis of relevant laws and regulations, as well as interviews with practitioners in the field. The results of the study indicate that there is regulatory disharmony that has an impact on the loss of the strategic function of general dentists in the national health service system. Therefore, policy harmonization is needed between BPJS regulations and the Health Law to ensure the sustainability of services and protection for the general dentist profession in Indonesia.